Interaction between effortful control and parenting as factors of child mental health - E. N. Petrenko; E. A. Kozlova; S. V. Loginova; H. R. Slobodskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The study examined interactions between parenting and child effortful control in the prediction of problem behavior in Russian preschoolers in parent reports of 28-year-old children (N = 652). Effortful Control and its components, inhibitory control, attentional control, low-intensity pleasure, and perceptual sensitivity, were measured by the Very Short Form of the Children’s Behavior Questionnaire (CBQ-VS). Positive parenting, punishment, and inconsistent discipline were measured by the Alabama Parenting QuestionnairePreschool Revision (APQ-R). Externalizing problems, internalizing problems, total difficulties, and impact of problems on the child’s life were measured by the Strengths and Difficulties Questionnaire (SDQ). The results indicated that effortful control and perceptual sensitivity interacted with parental punishment to predict externalizing problems and total difficulties such that temperament was more strongly related to problem behavior when parents used more punishment. In a similar way, inhibitory control was more strongly related to externalizing problems and their impact on the child’s life when parents used more punishment. The majority of moderating effects were consistent with the diathesis-stress or dual risk model. That is, temperament was more strongly related to externalizing and internalizing problems and their impact on the child’s life when parents used more punishment and were inconsistent in their use of discipline.